2021
DOI: 10.1002/jemt.23838
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet light accelerates the degradation of polyethylene plastics

Abstract: Polyethylene plastics are widely used in daily life in the packaging of foodstuffs, pharmaceuticals, cosmetics, detergents, and chemicals. In this study, low‐density polyethylene (LDPE) was exposed to an ultraviolet (UV) fluorescence lamp in simulated aging and degradation experiments. Ultraviolet degradation mechanisms were investigated on the surface after sunlight and UV lamp exposure. The plastic surfaces' molecular and surface degradation results were compared with their Fourier Transform Infrared‐Attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…25,38 We caution that changes in the bulk properties may not be representative of natural environmental processes and that the weathering mechanisms may differ. 59 This may be particularly relevant as UV-C is often used to rapidly weather microplastics for contaminant sorption studies 23,60,61 despite not reflecting terrestrial conditions (Figure S1). 59 Nonetheless, we propose that the multivariate approach described here can be used to photochemically age environmental microplastics.…”
Section: Natural and Uv-c Accelerated Weatheringmentioning
confidence: 99%
See 1 more Smart Citation
“…25,38 We caution that changes in the bulk properties may not be representative of natural environmental processes and that the weathering mechanisms may differ. 59 This may be particularly relevant as UV-C is often used to rapidly weather microplastics for contaminant sorption studies 23,60,61 despite not reflecting terrestrial conditions (Figure S1). 59 Nonetheless, we propose that the multivariate approach described here can be used to photochemically age environmental microplastics.…”
Section: Natural and Uv-c Accelerated Weatheringmentioning
confidence: 99%
“…59 This may be particularly relevant as UV-C is often used to rapidly weather microplastics for contaminant sorption studies 23,60,61 despite not reflecting terrestrial conditions (Figure S1). 59 Nonetheless, we propose that the multivariate approach described here can be used to photochemically age environmental microplastics.…”
Section: Natural and Uv-c Accelerated Weatheringmentioning
confidence: 99%
“…Ultraviolet light in natural light is located in the most deleterious radiation range for organic compounds: 295-385 nm [15,30,31], so it is regarded and proved as the most critical factor for failure of the UHMWPE fiber. Do gon [32] reported the controlling step that induces the degradation by UV. It is suggested that, after the molecular bond strengths' energy limit surpasses UV energy absorption, degradation takes place through the free radical formation.…”
Section: Discussionmentioning
confidence: 99%
“…The process can be sped up by conducting the UV exposure continuously and using high UV intensities but kept within natural ranges. However, shorter wavelengths are more effective at degrading plastic materials, and exposing them to light containing wavelengths that include the UVC region (200-280 nm) can significantly speed up the degradation process (Lee et al, 2020;Doğan, 2021), as can using intensities above natural levels. It should be noted that UVC exposure may lead to the formation of different degradation products and oxygenated radicals compared to UVB exposure (Doğan, 2021).…”
Section: Oxidative Degradationmentioning
confidence: 99%